Participatory management and sustainable use of groundwater: a review of the Andhra Pradesh Farmer-Managed Groundwater Systems project in India - Reddy, V. R.; Pavelic, Paul; Reddy, M. S. (International Water Management Institute, 2021)
This GRIPP Case Profile assesses whether the proactive involvement of rural communities in the management of groundwater positively contributes towards sustainable resource use. The assessment uses the long-term (2003-2013) Andhra Pradesh Farmer-Managed Groundwater Systems (APFAMGS) project in India as a case study. Implemented across seven districts, the assessment is based on a critical review and synthesis of existing literature and complementary field visits conducted five years after project closure. APFAMGS worked towards creating awareness and bringing about behavioral change to achieve sustainable groundwater use, primarily for irrigation. The approach focused on knowledge transfer and capacity building to set up participatory processes conducive to informal management measures, and technologies supporting participatory hydrological monitoring and crop water budgeting. In addition, awareness creation in relation to demand as well as supply side management options was critical. The analysis suggests that APFAMGS has helped in filling the knowledge and information gaps on groundwater resources among local farming communities. Some degree of long-term reduction in groundwater pumping was observed, but the attribution to the project is not clear, and effects on reducing groundwater level declines may be limited and localized. The APFAMGS approach of participatory groundwater management (PGM) fell short in terms of equity considerations, with implications for the institutional sustainability of the approach. The study provides policy guidance for adopting more inclusive PGM-based institutions on a wider scale.